Expanding social protection in developing countries: A gender perspective - Rania Antonopoulos (Levy Economics Institute of Bard College, 2013)
This paper discusses social protection initiatives in the context of developing countries and explores the opportunities they present for promoting a gender-equality agenda and women's empowerment. The paper begins with a brief introduction on the emergence of social protection (SP) and how it is linked to economic and social policy. Next, it reviews the context, concepts, and definitions relevant to SP policies and identifies gender-specific social and economic risks and corresponding SP instruments, drawing on country-level experiences. The thrust of the paper is to explore how SP instruments can help or hinder the process of altering rigid gendered roles, and offers a critical evaluation of SP interventions from the standpoint of women's inclusion in economic life. Conditional cash transfers and employment guarantee programs are discussed in detail. An extensive annotated bibliography accompanies this paper as a resource for researchers and practitioners.
Keywords: J13; J16; J18; O1; O11; O15; O19; 330; social protection; social assistance; gender; women; public works programs; conditional cash transfers; development; employment guarantee programs; social protection floor initiative; developing countries